Molecular characterization of sesame germplasms of West Bengal, India using RAPD markers - Saha, Soumen; Dhar, Tarak Nath; Ghosh, Parthadeb; Dey, Tulsi (Acta Biologica Szegediensis, 2019)
The aim of this research was to assess the genetic diversity of sesame (Sesamum indicum L.) and also to reveal the genetic relationships using the Random Amplified Polymorphic DNA (RAPD) markers. Fifteen sesame germplasms were collected from seven districts or four zones of West Bengal, India. A high genetic diversity was revealed by ten RAPD primers within and among the fifteen germplasms. The value of Jaccard’s similarity coefficients among and within the fifteen germplasms ranged from 0.287 to 0.725 which indicated high degree of genetic variability. Cluster analysis using Unweighted Pair Group Method with Arithmetic Mean (UPGMA) grouped all the germplasms into three main clusters. Analysis of various genetic diversity indices strongly indicated high level of genetic diversity among the populations of four different regions. UPGMA analysis of four populations resulted into two groups and the results of Principal Coordinates Analysis (PCoA) depicted a clear distinction among the germplasms.